Analysis of Learning Outcomes Module Material for Madrasah Ibtidaiyah Teachers of Teacher Professional Education in Position - Fitri Muthmainnah; Budiyono Budiyono (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines the analysis of learning outcomes for the deepening module of Madrasah Ibtidaiyah (Islamic Primary Schools) teachers in teacher professional education in position. The research method used is a qualitative method with a case study approach. The first findings show that the LMS PPG Daljab operational system phase 1 in 2022 has slightly changed or improved from 2021 to 2022. There are several things that must be fulfilled by lecturers and students, namely there are pretests, study contracts, resumes, analysis of teaching materials, analysis material, formative tests, module final tests organized by the center of the matter. Second, there are eight of the thirty Madrasah Ibtidaiyah teachers who must take remedial, seven students repeat the learning and learning theory module with an average value of 66.56 and then two students in the teacher professional development module with an average score of 66.91 and two students in the learning evaluation module with an average score of 60.58. Based on these data, some Madrasah Ibtidaiyah teachers still encounter problems in mastering learning and learning theory, while the ability is one of the important factors in determining learning success.